Optimization of process parameters of friction stir welded joints of marine grade AA 5083. (2021) - Sahu, Mrinal; Paul, Atanu; Ganguly, Subhas
Abstract: Friction Stir Welding is an innovative solid-state joining technique commonly utilized in industries. It is a combination of highly multifaceted process utilizing several coupled mechanisms. Although, large number of researchers are working in this field to reveal the maturity of the process evolving many plausible application and materials. Still the process needs intensive study to optimize production procedures that will yield high quality stronger welds from the stirring action of the tool and pin into the weld plate material. In this part of the research the study to know the influence process parameters and tool pin geometry on friction stir welding (FSW) of marine grade aluminium (5083) especially in reference to microstructure and mechanical properties of weld has been highlighted so as to optimize the welding parameters along with the tool geometry. Tensile properties of the joints have been studied and their correlations with the process parameters along with the tool parameters have been investigated. The highest joint efficiency of 75.67% efficiency with the ultimate tensile strength (UTS) of 212 MPa was noted in the case of FSW joint fabricated by T1 tool with 1000 rotational speed and 28 mm per minute of welding speed. Also, microstructures of various zones of FSW sample have been evolved and correlated with the process parameters which explains the dynamic recrystallization process at the nugget zone of FSW joint.